1992
DOI: 10.1016/0378-1097(92)90453-u
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis of Leptospirillum ferrooxidans and other acidophilic chemolithotrophs: comparison with the Escherichia coli chemosensory system

Abstract: Ni2+, Fe2+ and Cu2+ were attractants and aspartate was an apparent repellent for Leptospirillum ferrooxidans, a behaviour opposite to that for Escherichia coli. Membranes from L. ferrooxidans contained proteins with a molecular mass in the range of 80 kDa which were methylated in vitro. Methylation was stimulated in the presence of a membrane-free extract from E. coli, showing the response pattern expected for L. ferrooxidans, increased methylation by Ni2+, and demethylation by aspartate. This suggests the exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…The excreted organic compounds are assumed to be inhibitory to lithotrophic bacteria (Tuttle 10nml0.0kU 4.20E3 0488^40 and Dugan, 1976;Matin, 1978;Harrison, 1984;Wichlacz and Thompson, 1988). This hypothesis was supported by a recent study by Acuna et al (1992). They demonstrated in their work on chemotaxis of L. ferrooxidans that the amino acid aspartate is a repellent.…”
Section: Resultsmentioning
confidence: 59%
“…The excreted organic compounds are assumed to be inhibitory to lithotrophic bacteria (Tuttle 10nml0.0kU 4.20E3 0488^40 and Dugan, 1976;Matin, 1978;Harrison, 1984;Wichlacz and Thompson, 1988). This hypothesis was supported by a recent study by Acuna et al (1992). They demonstrated in their work on chemotaxis of L. ferrooxidans that the amino acid aspartate is a repellent.…”
Section: Resultsmentioning
confidence: 59%
“…It has been shown that both Leptospirillum group II and III possess a chemotaxis system and a flagellar operon [32] . L. ferrooxidans can sense substrates via its chemotaxis system [33] . In addition, EPS production by cells of L. ferrooxidans is generally higher than by cells of At.…”
Section: Initial Attachment To Pyrite By Pure and Mixed Culturesmentioning
confidence: 99%
“…ferrooxidans and A. ferrooxidans possess chemotaxis systems for sensing Fe(II), which might function to identify specific sites on pyrite surfaces for attachment [308,309]. Quorum sensing functions in bioleaching bacterium allow for swarming behavior on metal sulfides and play a key role in biofilm formation, enhancing dissolution of the mineral substrate [310][311][312][313][314][315].…”
Section: Attachment Of Extreme Thermoacidophiles To Surfacesmentioning
confidence: 99%